Monoclonal Antibodies Aggregation during Administration to Patients and the Role of Pharmaceutical Excipients - Almira, Deta; Nurcahya, Bekti Meilani; Rahmawati, Fita; Laksitorini, Marlyn Dian (Journal of Food and Pharmaceutical Sciences, 2025)
Monoclonal antibodies (mAbs) are powerful therapeutic agents known for their high specificity and effectiveness in treating complex diseases. Yet, one of their major challenges is their tendency to aggregate, which can reduce treatment efficacy and even trigger unwanted immune responses. This review focuses on how pharmaceutical excipients can help prevent antibody aggregation, particularly during the drug administration process, a phase often overlooked. We conducted a systematic literature search using Scopus, PubMed, and ScienceDirect, targeting studies on excipients and aggregation in therapeutic proteins. After applying the selection criteria, six original research articles were analyzed. The findings reveal that several excipients—such as L-arginine, polysorbates, trehalose derivatives, proline analogs, and cyclodextrins—can effectively stabilize mAbs. They work by reducing interfacial stress, minimizing protein–protein interactions, and preserving antibody structure during stress conditions like infusion or inhalation. These insights highlight the importance of choosing the right excipient based on the administration route to ensure antibody stability and therapeutic impact. By shifting the focus from formulation to administration, this review provides a practical perspective that can support the development of safer and more effective mAb therapies.